School gardens and biofertilization as a strategy towards climate change mitigation and adaptation in Costa Rica = Huertas escolares y biofertilización como estrategia hacia la mitigación y adaptación al cambio climático en Costa Rica - Rojas Alvarado, Carlos Alonso 1976-; Rojas, Pedro A 1962-; Nakajima, Shiori; Doss, Robin G. 1987-; Rodríguez Mora, Karina María 1989- (2021)
School gardens are important for the conceptual integration of topics such as climate change. Using a biofertilization experiment in a school garden, we evaluated four experimental treatments and the student knowledge to some sustainable practices. Solid bio-fertilization was more effective than liquid treatments. The effect of the garden establishment was positive on the knowledge demonstrated by students. Similar activities are recommend-ed in the context of primary education in Costa Rica.
Las huertas son espacios importantes para la integración conceptual del cambio climático en la educación. Con base en un experimento de biofertilización en una huerta escolar se evaluaron cuatro tratamientos experimentales y el efecto de la huerta sobre cono-cimientos de estudiantes a prácticas de sostenibilidad. La fertilización sólida fue más efectiva que los tratamientos líquidos. El efecto de la huerta sobre el conocimiento de los niños fue positivo. Actividades similares son recomendadas.
En Revista Intersedes, vol. 22, no. 45, (Enero-Julio 2021)
Descripción basada en el contenido visto el 29 de mayo, 2025
También disponible en formato EPUB